Skutele iz miocenskih skladov Slovenije - Mikuž, Vasja (Geologija, 2009)
In the article are considered sea urchins of family Scutellidae found in Slovenia. Two forms were determined: species Parascutella gibbercula (de Serres, 1829), occurring as a rule in Middle Miocene - Badenian lithothamnian limestones of Dolenjska and Štajerska, and species Parascutella paulensis (Agassiz, 1841), in Lower Miocene Govce clastic beds of Štajerska.
Keywords: fosili; miocen; morski ježki; skutele; Slovenia; Slovenija